The use of three-dimensional biometric Foot and Ankle Offset to predict additional realignment procedures in total ankle replacement. Issue 7 (October 2022) - de Cesar Netto, Cesar; Day, Jonathan; Godoy-Santos, Alexandre Leme; Roney, Andrew; Barbachan Mansur, Nacime S.; Lintz, Francois; Ellis, Scott J.; Demetracopoulos, Constantine A.
Highlights: The use of weightbearing CT (WBCT) measurements to assess multiplanar deformity is a valuable tool in surgical planning. We evaluated 21 patients who underwent TAR using the Foot and Ankle Offset (FAO) and the need for additional alignment procedures. FAO was more pronounced in valgus malalignment and correlated with the number of osseous realignment procedures needed (p=.001). 3D biometrics and WBCT semi-automatic measurements may improve the assessment and surgical planning for patients undergoing TAR. Abstract: Background: Decision to perform associated corrective alignment procedures in patients undergoing total ankle replacement (TAR) is commonly made intraoperatively. The Foot and Ankle Offset (FAO) can evaluate multiplanar deformity and be an effective instrument in surgical planning. This study objective was to assess the ability of this tool to predict the need for additional realignment procedures at the time of TAR. Methods: In this retrospective study, we enrolled 21 patients who underwent TAR and had preoperative WBCT studies. Two independent and blinded observers calculated the preoperative FAO using dedicated software. FAO measurements were compared between the different alignment groups (physiological alignment, valgus and varus). A multivariate regression analysis was used to assess the correlation between performed realignment procedures and FAO values. Results: Mean preoperative FAO was 4.4% (95%CI = 1.4–7.5). The number of osseous realignment procedures needed was found to correlate positively and significantly with FAO (p = .001). The number of osseus procedures needed was significantly higher in patients with valgus malalignment (p = .009). Patients with valgus malalignment needing a medial column procedure had a relative risk of 6.3 when compared to varus malalignment patients (p = .02). Conclusion: The number of additional bony realignment procedures performed at the time of TAR significantly correlated with preoperative FAO and that the number of osseus procedures needed was significantly higher in patients with valgus malalignment. Such biometric tools may enhance the preoperative assessment and surgical planning for patients undergoing TAR, with the potential to optimize surgical outcomes.